Pertanggungjawaban Pidana Korupsi Di Sektor Badan Usaha Milik Negara - Rini Apriyani; Adi Nurhamidi; Ivan Zairani Lisi (Masyarakat Hukum Pidana dan Kriminologi Indonesia, 2022)
State-Owned Enterprises are legal entities created by the Government using funds taken from the State Revenue Budget (APBN) as a form of state effort to meet the needs and benefits of the Indonesian people, but in carrying out their business several problems arise related to the limitations of the flow of state finances in the finances of the Agency. State-Owned Enterprises, which often this lack of clarity causes several problems related to legal qualifications due to business actions that are not profitable for State-Owned Enterprises that lead to criminal acts of corruption. detrimental to state finances. The Law Number 40 of 2007 concerning Limited Liability Companies has clearly adopted the legal principle of Immunity Doctrine against the structure of Limited Liability Companies, namely the Business Judgemaent Rule. there are several aspects to qualify as an action in accordance with the principles of the Business Judgment Rule. State-Owned Enterprises in carrying out business are subject to the Limited Liability Company law, but in terms of finances, it refers to the regulation on State Finance, this is the point of problems in the State-Owned Enterprises sector